2022
DOI: 10.3390/foods11050669
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Residues of Pyraclostrobin in Rosa roxburghii and Soil under Field Conditions

Abstract: Rosa roxburghii has been widely planted in China. Powdery mildew is the most serious disease of R. roxburghii cultivation. Pyraclostrobin was widely used as a novel fungicide to control powdery mildew of R. roxburghii. To assess the safety of pyraclostrobin for use on R. roxburghii fruits, its residue rapid analysis as well as an investigation on its dissipation behaviors and terminal residues in R. roxburghii and soil under field conditions were carried out. The QuEChERS method was simplified using LC–MS/MS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, in recent studies, very few methods have been developed to detect the two drugs together [ 13 , 26 ]. Single-drug assays are easier to develop because of their simpler instrument development methods [ 27 , 28 , 29 , 30 , 31 , 32 ]. Therefore, this study developed an LC-MS/MS technique that can detect boscalid and pyraclostrobin simultaneously, which optimized the drug retention time and greatly shortened the detection time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent studies, very few methods have been developed to detect the two drugs together [ 13 , 26 ]. Single-drug assays are easier to develop because of their simpler instrument development methods [ 27 , 28 , 29 , 30 , 31 , 32 ]. Therefore, this study developed an LC-MS/MS technique that can detect boscalid and pyraclostrobin simultaneously, which optimized the drug retention time and greatly shortened the detection time.…”
Section: Resultsmentioning
confidence: 99%
“…The half-life of boscalid in soil can be as high as 182 d (loamy sand soil) and as low as 9.7 d (grape field soil) [ 8 , 13 ]. The half-life of pyraclostrobin in soil can be 3.86–13.70 d [ 13 , 30 ]. In addition, the half-lives of boscalid were 1.90–2.01 d and 18.1–18.8 d, and the half-lives of pyraclostrobin were 1.62–1.73 d and 17.8–25.9 d, respectively, on greenhouse dill and grape [ 13 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Selecting the right equipment for appropriate pesticide application is important for application efficiency and minimization of the loss of spray solution [132], as well as the reduction of pesticide residuals in the environment and the exposure of and risks to residents and farmers [20,32,133]. Han Li et al [31] discussed the different operating parameters which could obtain a better reference for the determination of field operating parameters, and technical references for field pesticide application and the results of the study indicated that, compared to traditional spraying machinery, unmanned aerial sprayers had advantages of more uniform liquid deposition distribution and better penetration, providing a technical reference for field spray operations and the establishment of a uniform standard for pesticide application technology.…”
Section: The Impact Of Pesticide Application Methods On Exposure and ...mentioning
confidence: 99%
“…The higher extraction efficiency was obtained using ACN containing 1% HAc and a combination of MgSO 4 , NaCl, and NaOAc (4:1:1, w/w). Much less commonly, some authors have applied the QuEChERS method without including extraction salts [41,42,56]. Evidently, these authors did not add water to the soil sample as a hydration step.…”
Section: Modifications Of the Salting-out Effectmentioning
confidence: 99%
“…Consequently, dSPE is a shorter, simpler and more environmentally friendly procedure than conventional SPE. As in the most popular versions, anhydrous MgSO 4 and PSA have been effectively used during pesticide analysis in soil samples [14,17,19,22,53,54,56]. For example, Słowik-Borowiec et al [54] recently used 180 mg of MgSO 4 and 30 mg of PSA per mL of extract for the determination of 94 multiclass pesticides and 13 polycyclic aromatic hydrocarbons in soil samples.…”
Section: The D-spe Approachmentioning
confidence: 99%